(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2025)
This study aims to explore The aim of the current research is to identify the degree of use of technology and its means in kindergartens in the city of Damascus and the difficulties they face, in addition to developing a proposed model for the use of technology. The researcher used the descriptive analytical method, and the research tool was a questionnaire directed to the kindergarten teacher consisting of two sections, the first is demographic variables and the second section is the degree of use and difficulties. The study sample included (44) public kindergarten teachers and (120) private kindergarten teachers. The study concluded that the degree of technology use was average in general and was higher in private kindergartens. Weak technical support was one of the most prominent difficulties that the kindergarten suffers from in using technology. .